Perancangan Sistem Informasi Penanganan Penyakit HIV/AIDS Berbasis Web Menggunakan Pemodelan UML - Herawati, Rahma; Voutama, Apriade (INFORMAL: Informatics Journal, 2024)
The development of life in the present cannot be separated from the progress and sophistication of various technologies that move and run in balance towards better directions and benefits. One form of technological progress that occurs is the launch and creation of various websites in various fields including health. The website presented in this Journal is the Life Changing website. This website was launched and presented with a focus and context in which the information in it explains how to prevent the spread and transmission of HIV/AIDS. HIV/AIDS is a disease that attacks the human immune system. Human Immunodeficiency Virus that attacks the human immune system has an impact on the decline of the immune system which causes AIDS (Acquired Immune Deficiency Syndrome). The process of making this website uses several methods including: planning, system analysis, system development with UML modeling, and implementation. In the development of the system using UML modeling in order to describe the system to be designed using diagrams, which makes it easier for readers to understand the overall picture of the website handling & prevention of HIV / AIDS.